A Feed-Forward Circuit of Endogenous PGC-1α and Estrogen Related Receptor α Regulates the Neuronal Electron Transport Chain - Bakshi, Rachit (Parkinsons Dis, 2016)
Peroxisome proliferator-activated receptor  γ coactivator 1α (PGC-1α) is a central regulator of cellular and mitochondrial metabolism. Cellular bioenergetics are critically important in “energy-guzzling” neurons, but the components and wiring of the transcriptional circuit through which PGC-1α regulates the neuronal electron transport chain have not been established. This information may be vital for restoring neuronal bioenergetics gene expression that is compromised during incipient Parkinson's neuropathology and in aging-dependent brain diseases. Here we delineate a neuronal transcriptional circuit controlled by endogenous PGC-1α. We show that a feed-forward circuit of endogenous neuronal PGC-1α and the orphan nuclear estrogen-related receptor α (ERRα) activates the nuclear-encoded mitochondrial electron transport chain. PGC-1α not only trans-activated expression of ERRα, but also coactivated ERRα target genes in complexes I, II, IV, and V of the neuronal electron transport chain via association with evolutionary conserved ERRα promoter binding motifs. Chemical activation of this transcriptional program induced transcription of the neuronal electron transport chain. These data highlight a neuronal transcriptional circuit regulated by PGC-1α that can be therapeutically targeted for Parkinson's and other neurodegenerative diseases.